Changing epidemiology of Infant Meningococcal Disease after the introduction of meningococcal serogroup C vaccine in Italy, 2006–2014. Issue 31 (17th July 2015) - Stefanelli, P.; Fazio, C.; Neri, A.; Boros, S.; Renna, G.; Pompa, M.G.; ,
Abstract: Background: In Italy, the incidence of Invasive Meningococcal Disease (IMD) was around 0.28 per 100, 000 over the last years. Since the risk IMD is usually high among infants aged less than 1 year, we decided to evaluate the trend of IMD cases reported between 2006 and 2014 in this age group. In particular, the study aim was to describe the main characteristics of IMD cases in infants following the introduction of MCC vaccine (2005) and to estimate the number of cases which are potentially preventable through early vaccination. Methods: The National Surveillance System of Bacterial Meningitis was established in 1994 and in 2007 was extended to all invasive bacterial diseases. Clinical data and isolates and/or clinical samples are collected from hospitalized patients throughout the country. IMD cases are reported by clinicians to the local health authorities, and samples are sent to the Reference Laboratory at the Istituto Superiore di Sanità for further characterization and storage at −80 °C. In particular, serogroup identification is obtained by agglutination with commercial antisera or by multiplex PCR. Results: The annual incidence for infants <1 year old remained rather stable of 3.6 per 100, 000, with several upward and downward oscillations and a peak in 2010. The incidence of IMD among infants was more than 10 times higher than the overall rate of IMD observed in Italy. Finally, serogroup B was more frequently detected among infants aged <1 year, accounting for 65% of the total ( p  < 0.01). Conclusions: During the study period, IMD incidence reported among infants aged less than one year old was 10 times higher than the overall rate, and serogroup B was the most commonly detected over time. The long-term impact of meningococcal C conjugate vaccine and the effect of the introduction of meningococcal B vaccination among infants need to be evaluated.